Methodological Approach for a New Economic Geography of the Territorial Cohesion in Europe and Italy - Maria Prezioso (Bollettino della Società Geografica Italiana)
In this time, the Territorial Impact Assessment (TIA) is the best process to support the development of global/local sustainable policies. It identifies territorial/spatial problems and objectives (by several ex ante and ex post steps), the main political/programming scenarios and options measuring impacts on economic, environmental, cultural and social fields. It outlines advantages and disadvantages for each policy option and examines all possible synergies and trade-offs on the base of the territorial context (geographical diversity). In order to study the integration of the Cohesion Policy objectives 2020 and post within the Italian development programs (national and regional), the evaluation of Territorial Cohesion in Italian regions by TIA was applied. The STeMA-TIA model has been devised to support an integrated strategic vision of general, territorialised and sectoral policies at NUT1, 2 and 3 decision-making levels. This assessment tool was created as part of the territorial dimension evaluation of the European Strategies. In the context of ongoing research (PRIN 2015), the method and the ex ante application are illustrated in the following in supporting of attended results of first step, which was critically discussed at European level, too.